Zootechnical performance and quality of filet tambaqui Colossoma macropomum fed with a diet supplemented cyanophyceae Spirulina platensis - Rafael Lustosa Maciel (2014)
Tambaqui, Colossoma macropomum, is one of the most important fishery resources in the Amazon region and is the most cultivated native fish in Brazil due to omnivorous and its rusticity. Alternative ingredients for feed formulation are needed to maximize strength and weight gain of the animals when cultured at high stocking densities. The cyanophyceae Spirulina platensis is a microalgae with high nutritional, value rich in protein and vitamins, which has been used as an additive in diets for various species of fish. The aim of this study was to monitor the livestock development and the quality of the steak fry tambaqui fed diets with high inclusion levels of S. platensis. The study was divided into two phases. In the first phase, which lasted 60 days, we adopted a stocking density of 40 fish.m-2, while in the second phase, lasting 105 days, this value was halved. The feeding of animals was given four times a day with commercial diet with added 20% Spirulina (T1), with feed added Spirulina 40% (T2) and as a control (C) a commercial ration containing 50% was used crude protein (CP). At the end of the first phase, no statistically significant difference in survival or final biomass was observed, while the highest average final weight was observed in the control group (15.18 Â 0.57 g) was significantly higher than obtained in T1 (12 , 00 Â 1.40 g) and T2 (12.09 Â 1.22 g). In the second step also no statistically significant differences between treatments for the survival and final biomass was observed. As for the final average weight the highest value was again observed in the control, with 84.86 Â 8.44 g, significantly higher than those in T1 (75.87 Â 6.00) and T2 (70.68 Â 6.16). Quality analysis of fillet showed that fish which fed the diet containing 20% Spirulina (T2) presented protein level (17.78 Â 0.04%), lipid (1.23 Â 0.04) and energy (82.13 Â 0.18 Kcal/100g), significantly higher than the others treatments. We conclude that feeding tambaqui with Spirulina does not affect survival neither final biomass, in addition to increasing the nutritional value of fillet.